Stereotactic Body Radiotherapy: A Review of its Application in Prostate Cancer - Mohammad A. Attar (Journal of King Abdulaziz University: Medical Sciences, 2023)
In the recent years, remarkable progress in the field of radiotherapy has been made, especially in treatment delivery techniques. Close attention has been paid to prostate cancer, in particular because of its high incidence and the potential curability. During the last decades, strategies of radiotherapy of prostate cancer have improved with regard to dose escalation, hypo-fractionation, high-dose-rate brachytherapy, and the introduction of modern techniques such as Intensity Modulated Radiation Therapy and Stereotactic Body Radiation Therapy. Stereotactic radiotherapy for prostate cancer is used to deliver a higher dose to the prostate with better sparing for bladder and rectum, due to a high level of precision and smaller required planning target volume, in reduced number of fractions, either exclusively for early localized disease or as a boost after External Beam Radiation Therapy for more advanced localized disease. Recent clinical data showed that Stereotactic Body Radiation Therapy provides acceptable toxicities and encouraging results of biological control. More trials with long-term follow-up are required to evaluate the late toxicities and its efficacy for the consideration of Stereotactic Body Radiation Therapy as a treatment option for patients with localized prostate cancer.